Academic Pipeline Programs Diversifying Pathways from the Bachelor's to the Professoriate - Byrd, Curtis D. (Lever Press, 2021)
Academic pipeline programs are critical to effectively support the steady increase of diverse students entering the academy. Academic Pipeline Programs: Diversifying Bachelor's to the Professoriate describes best practices of successful academic government and privately funded pre-collegiate, collegiate, graduate, and postdoctoral/faculty development pipeline programs. The authors explore 21 hallmark academic pipeline programs using their THRIVE index: Type, History, Research, Inclusion, Identity, Voice, and Expectation. The final chapter of the book offers information for using and starting similar programs. The appendix offers an interactive Geographic Information System (GIS) mapped database of programs using the THRIVE index. This book will equip parents, high school counselors, college advisors, faculty, department chairs, and higher education administrators to identify academic pipeline programs that fit their needs. Readers will also learn about how academic pipeline programs are situated within an institutional or organizational change model.